ENGLISH LANGUAGE TEACHING (ELT) POLICY IN THE AI ERA: CHALLENGES AND OPPORTUNITIES - Pramerta, I Gde Putu Agus (Jurnal Santiaji Pendidikan (JSP), 2025)
In recent years, the rapid advancement of Artificial Intelligence (AI) has brought significant implications for English Language Teaching (ELT). This study explores school principals and English teachers’ perspectives on the integration of AI in ELT within the context of existing policy. It aims to examine how teachers perceive current ELT policies in the AI era, the challenges they face in implementing AI-based tools, and the opportunities to bridge the gap between policy and classroom practice. Using a qualitative descriptive approach, survey and structured interview were conducted with multiple informants across different educational levels, involving respondents with diverse professional backgrounds: English teachers, vice headmasters for academic and curriculum affairs, and headmasters. The survey results indicate that respondents strongly understand current English language learning policies and agree on the urgency of integrating AI developments, digital literacy, and academic literacy into policy and planning. However, while most believe AI-based policies can have a positive impact, they note that current policies are not yet fully supportive of AI integration. Thematic analysis revealed three key findings: (1) the absence of clear and comprehensive ELT policy frameworks addressing AI integration, (2) teachers’ proactive adaptation through self-initiated practices and resource exploration, and (3) persistent challenges related to digital literacy, infrastructure, and ethical considerations. These results indicate that while respondents demonstrate strong agency in navigating AI-based innovations, sustainable integration requires well-defined policies and needs-based professional development.